Prototipe Jemuran Pakaian Otomatis Menggunakan Wemos D1R2 Dengan Notifikasi Suara dan Email Dari Thinger.io - Ardi Prawido Ramadhan; Jufrizel; Putut Son Maria; Hilman Zarory (Jurnal Sistem Cerdas, 2022)
Abstract— The Meteorology, Climatology and Geophysics Agency (BMKG) predicts that the start of the rainy season in Indonesia will occur from September to November 2022 with the peak of the rainy season expected to occur in December 2022 and January 2023. The rainy season that will occur will certainly hamper the process of drying clothes and inefficient use of time because they have to lift clothes when it rains and dry them again when the rain stops. Another problem is when you are sleeping or traveling so it is not possible to remove your clothes when it is going to rain. As a result the clothes become damp or wet. The purpose of this research is to prevent damp/wet clothes again when it rains and to save time when lifting and drying clothes during the rainy season. The method used in this study is the Research and Development (R&D) method. It begins with reviewing previous research so that it can determine what hardware is needed, followed by making a flowchart then assembled into a prototype tool that is integrated with the Internet of Things (IoT). The test results show that this automatic clothesline can remove the clothes from the room automatically when the rain sensor and the LDR sensor detect rain indications such as cloudy and drizzling, and vice versa will put clothes in automatically when the weather is cloudy or raining. The stepper motor is coupled with a linear actuator which functions to move the clothesline in and out. There are sound notifications and email messages from Thinger.io when the clothesline has entered or left. The prototype is equipped with an emergency system so that it can insert and remove the clothesline when the sensor is damaged.